KEWENANGAN DPD DALAM SISTEM KETATANEGARAAN INDONESIA PASCA PUTUSAN MAHKAMAH KONSTITUSI - Ni Kadek Riza Sartika Setiawati; Nyoman Mas Aryani (Kertha Negara : Journal Ilmu Hukum, 2014)
This writing shall be entitled as "AUTHORITY OF DPD IN INDONESIAN CONSTITUTIONAL SYSTEM AFTER THE CONSTITUTIONAL COURT RULING". This writing shall employ normative legal research combined with statutory, historical, and conceptual approach respectively. DPD shall be regarded as regional senate which is comprised upon senators who are elected through general election without any means of political party involvement regional senate shall also embed the function of legislation, consideration, and supervision.